FROM OBSERVATION TO PROFESSIONAL ASPIRATION: TRANSFORMING FIRST STEPS IN PRE-SERVICE TEACHER TRAINING - Moskalets, Olena; Tsapro, Galyna; Vinnikova, Liliia; Gryshchenko, Olena (The Modern Higher Education Review, 2025)
This nine-year longitudinal study reports on the redesign of early field practice in a pre-service English language teaching course at Borys Grinchenko Kyiv Metropolitan University. Initially grounded in the principles of the New Generation School Teacher project, the course was later revised to align more closely with students’ needs and the real-life teaching context. The intervention replaced early school-based observation with structured, guided observation of live lessons delivered by more advanced peers on university premises, with Year 2 students participating as learners and observers and Year 3 students alternating roles as student-teachers and peers. The change followed the growing gap between what early school observation was meant to achieve and how students actually responded. In the first cohorts of pre-SETT students, many found that lessons they observed relied on rigid, teacher-centred routines. Instead of inspiring confidence, this experience often confirmed their doubts about teaching as a career. Mixed-method survey data from three tracked cohorts show rising satisfaction with observation practice and stronger links between engagement, perceived preparedness, and readiness to teach. Internal consistency measures (Cronbach’s α) were moderate to good across instruments; correlations between interest in observation and both willingness to teach and short-term readiness strengthened as the peer-based model matured. In 2022/23, satisfaction with the peer-led observation days was high; by 2024/25, graduates rated their preparation and school-based practice positively, with over half positioning teaching as a plausible career pathway on the upper end of the scale. While the proportion of students unequivocally committing to school employment remains below the original NGST target, the university-based peer model demonstrably improves early engagement, builds a realistic teacher identity, and lowers the entry threshold for subsequent school practice, particularly under crisis constraints that restrict access to model classrooms. The findings suggest that guided peer observation offers a robust format for the first steps of Pre-SETT and should be combined with later school placements, while systemic measures beyond the university are required to address profession-level prestige and retention.